Compressive strength forecasting of rubberized lightweight foamed concrete with fresh density of 1250 kg/m3 during the hardening process utilizing elastic wave method - Lim, Kai Jun (2023)
As time has progressed, tyre waste has become an increasingly pressing environmental issue partly due to population growth. Nowadays, lightweight foamed concrete is extensively used in various industries, and tyre waste is being repurposed as crumb rubber to replace the fine aggregate to produce rubberized lightweight foamed concrete. Conducting the compressive strength test on the existing structure constructed using rubberized lightweight foamed concrete is important. However, the conventional method for testing the compressive strength of existing structures remains destructive. Thus, the research is mainly to determine the compressive strength of rubberized lightweight foam concrete through an innovative non-destructive method. In this research, the rubberized lightweight foamed concrete sample is subjected to two tests: the destructive test method (DT) and the non-destructive test method (NDT). In the destructive testing method, the compressive strength of the rubberized lightweight foamed concrete is obtained by applying the loading on it until the failure occurs using the compression test machine. The elastic wave method (NDT) is employed in this study. The change in P-wave properties has been investigated to correlate with the compressive strength obtained from the destructive test. Amplitude and velocity are two P-wave parameters with a high regression degree larger than 0.8 when correlated with compressive strength. This implies that the wave amplitude and wave velocity are suitable for forecasting the compressive strength of rubberized lightweight foamed concrete. However, wave amplitude is more reliable than wave velocity because its regression degree is significantly higher. In conclusion, rubberized lightweight foam concrete is a suitable construction material based on its performance. The non-destructive method can effectively forecast the compressive strength of rubberized lightweight foam concrete due to the higher regression degree.